Investigation of Warnings Regarding Driving and Machine Use in Summary of Product Characteristics and Patient Information Leaflets of Drugs Frequently Used in Psychiatry - AKICI, AHMET (GAZI UNIV, FAC MED, 2020)
Objective: This study aimed to investigate details of warnings about effects on ability to drive and use machines in the summary of product characteristics (SmPC) and patient information leaflet (PIL) of the drugs that are frequently used in psychiatry and have expected and undesirable effects in central nervous system. Methods: Current SmPCs/PILs of the ten most commonly prescribed drugs in Turkey were examined in detail. The information under the subheadings of effects on ability to drive and use machines in SmPC and driving and using machines in PILs was assessed in at least two different time periods via standard evaluation criteria. Results: SmPCs/PILs of 409 generic drugs were examined. While 80.2% of these generics had same warnings as their reference drugs, major differences were found in 8.3% of SmPCs and 8.1% of PILs, compared to that of originals. The active ingredients with major differences in SmPCs included venlafaxine (47.8%), risperidone (34.0%), sertraline (22.2%), and paroxetine (5.6%) whereas those having major differences in their PILs were paroxetine (72.2%), mirtazapine (52.0%), sertraline (22.2%) and venlafaxine (13.0%). Except paroxetine, all examined active ingredients were found to have consistent SmPCs and PILs in their warnings about driving and machine use. Conclusion: Although SmPCs/PILs of examined drugs overall seem compatible regarding the warnings of driving and machine use, it is noteworthy that warnings in SmPCs/PILs of considerable amount of reference drugs differed from their generics. The study findings indicate the need for a more rigorous approach to the standardization of the content within the SmPCs/PILs.
Keywords: Antidepressant; Antipsychotic; Generic; Summary of product characteristics; Patient information leaflet; ANTIDEPRESSANTS; PERFORMANCE; PSYCHOMOTOR; ABILITY; SAFE